Establishing Autonomous AUS-Quadrotor - Al Younes, Younes (2009)
A Master of Science Thesis in Mechatronics Submitted by Younes Al Younes Entitled, "Establishing Autonomous AUS-Quadrotor," October 2009. Available are both Soft and Hard Copies of the Thesis.